Public health impact of antihypertensive medication use on arterial blood pressure: A pooled cross-sectional analysis of population health surveys. - Diego Montano (PLoS ONE, 2023)
The early initiation of antihypertensive drug therapy is conceived as one of the most important public health interventions addressing cardiovascular risk in the population. However, the actual contribution of this public health intervention to reduce blood pressure (BP) at the population level is largely unknown. Hence, the aim of the present investigation is to estimate the potential public health effects of the use of antihypertensive medication on BP in the population aged 16 and older. Data from three population health surveys periodically conducted in the United States, England, and Scotland are analysed (N = 362,275). The secular trends of BP measurements and the potential public health impact of the use of antihypertensive medications on BP over time are analysed in a series of linear mixed models. Between 1992 and 2019, a secular trend of decreasing systolic and diastolic BP occurred (-16.24 99% CI [-16.80; -15.68] and -3.08 99% CI [-3.36; -2.80] mmHg, respectively). The potential public health impact of the use of antihypertensive medications in the period 1992-2019 on systolic BP was estimated to lie between -8.56 99% CI [-8.34; -8.77] and -8.68 99% CI [-8.33; -9.03] mmHg. Average reduction of diastolic BP was in the range of -5.56 99% CI [-5.71; -5.42] and -6.55 99% CI [-6.78; -6.32] mmHg. The observed changes in the distribution of BP measurements over time were found to be more strongly related to secular trends affecting the whole populations, rather than to increases in the proportion of individuals taking antihypertensive medications.